The legal framework of Islamic criminal law in Aceh with reference to application, challenges and way forward = Kerangka undang-undang jenayah Islam di Aceh merujuk kepada aplikasi, cabaran dan jalan kehadapan - Wan Muhammad, Ramizah; Abdul Salam, Khairunnasriah; Hussin, Nasimah (IIUM Press, International Islamic University Malaysia, 2018)
Aceh is a special province in Indonesia and different from other Indonesian provinces especially in the context of Shari'ah related laws. Aceh was granted special autonomy and legal right by the Indonesian central government in 2001 to fully apply Islamic law in the province. Generally, Islamic law which is applicable to Muslims in Indonesia is limited to personal laws just as in Malaysia. However, with the passage of time, Islamic law has expanded to include Islamic banking and finance. Besides that, Islamic law in Aceh is also extended to govern criminal matters which are in line with the motto of Aceh Islamic government to apply Islamic law in total or kaffah. Since 1999, the legal administration of Aceh has begun to gradually put in place the institutional framework to ensure that Islamic law is properly administered and implemented. Equally important, such framework is also aimed to ensure that punishments are fairly executed. This paper attempts to analyse the extent of the applicability of Islamic criminal law in Aceh. It is divided into three major parts. The first part discusses the phases in making Aceh an Islamic province and the roles played by Dinas Syariat Islam Aceh as the policy maker in implementing Islamic law as well as educating and training the public about the religion of Islam. The second part gives an overview on the Islamic criminal law and punishment provided in Qanun Aceh No.6/2014 on Hukum Jinayat (hereinafter Qanun Hukum Jinayat or “QHJ”) as well as the criminal procedural law concerning the methods of proof codified in Qanun Aceh No.7/2013 on Hukum Acara Jinayat (hereinafter “QAJ”). The third part of this paper highlights the challenges in the application and implementation of Islamic criminal law in Aceh, and accordingly provides recommendations for the improvement of the provisions in the QHJ and QAJ. Inputs from the interviews with the drafters of QHJ, namely Prof. Dr. Hamid Sarong and Prof. Dr Al Yasa are utilized in preparing this paper. In addition, inputs gathered from nongovernmental organizations (NGOs), namely Indonesian Syarie Lawyers Association (APSI) and Jaringan Masyarakat Sipil Peduli Syariah (JMSPS) are employed. The findings of this research are important in providing an in-depth understanding on the framework of Islamic criminal law in Aceh as well as in recognizing the flaws in its application or practical aspects of the law in Aceh. ******************************************************** Aceh merupakan sebuah Wilayah Istimewa di Indonesia dibandingkan dengan wilayah-wilayah lain dari segi pelaksanaan undang-undang Islam. Aceh diberi status Wilayah Istimewa yang berautonomi oleh Pemerintah Pusat Indonesia pada tahun 2001 untuk melaksanakan undang-undang Islam secara menyeluruh. Pemakaian dan pelaksanaan undang-undang Islam di Aceh tidak terhad pada Undang-undang jenayah tetapi telah meliputi bidang perbankan dan kewangan Islam. Sejak tahun 1999, Pentadbiran Undang-undang Aceh telah merangka undang-undang bagi memastikan undang-undang Islam dapat ditadbir dan dilaksanakan dengan baik. Selain itu juga, undang-undang yang dirangka juga turut bertujuan untuk memastikan hukuman yang berasaskan undang-undang Islam dapat dilaksanakan secara adil. Oleh itu, kajian dalam kertas kerja ini dibuat uuntuk menganalisa sejauh mana undang-undang jenayah Islam dilaksanakan di Aceh. Kertas ini terbahagi kepada tiga bahagan utama, yang mana bahagian pertama membincangkan latas belakang awal kewujudan wilayah Islam Aceh dan peranan yang dimainkan oleh Dinas Syariat Islam Aceh sebagai mpembuat dasar dalam pelaksanaan undang-undang Islam, mendidik serta menyediakan latihan kepada masyarakat umum di Aceh mengenai Islam. Bahagian kedua menyediakan gambaran umum tentang undang-undang jenayah dan hukuman dalam Islam sebagaimana termaktub dalam Qanun Aceh No.6/2014 berkenaan Hukum Jinayat (“Qanun Hukum Jinayat” atau “QHJ”) serta undang-undang prosedur jenayah berkenaan cara pembuktiaan jenayah sebagaimana yag termaktub dalam Qanun Aceh No.7/2013 berkenaan Hukum Acara Jinayat (“QAJ”). Bahagian ketiga kertas ini menekankan masalah atau cabaran yang dihadapi daam pelaksanaan undang-undang jenayah Islam di Aceh, serta menyediakan cadangan-cadangan bagi penambahbaikan peruntukan-peruntukan yang ada dalam QHJ dan QAJ. Maklumat hasil dari temuramah dengan Prof. Dr. Hamid Sarong dan Prof. Dr Al Yasa telah digunakan bagi menyiapkan makalah ini. Selain itu, maklumat yang diperolehi daripada organisasi bukan kerajaan iaitu Indonesian Syarie Lawyers Association (APSI) dan Jaringan Masyarakat Sipil Peduli Syariah (JMSPS) turut dimanfaatkan. Dapatan dari kajian ini penting bagi menyediakan kefahaman terhadap kerangka undang-undang jenayah Islam di Aceh serta mengenal pasti masalah dalam aspek peruntukan undang-undang tersebut atau pelaksanaannya di Aceh.